Health care staff perception of noise in neonatal intensive care units: a questionnaire survey from NeoNoise Project - Alberto Alves Carvalhais, Carlos (2021)
A hospital Neonatal Intensive Care Unit (NICU) is designed to treat premature infants who need special care. These kind of units have become quite sophisticated, with a sort of medical devices that support an array of health care staff, such, physicians, nurses, health technicians, etc. (Konkani & Oakley, 2012). Noise in NICU is recognized as an agent with negative implications on health and well-being of premature infants (Nicolau, Casal, Lopes, & Kronenberg, 2005) and health professionals (Carvalhais, Santos, Vieira da Silva, & Xavier, 2015). Noise in NICU, and its effects on patients and staff, such as physiological and psychological disorders, has become an important issue, particularly because in these case patients are mainly premature infants. Noise as a stressor does not only put pressure on the workers and may result in a higher error occurrence, but also affect in a negative way, the healing process of patients (Siegmann & Notbohm, 2013). Figure 1, presents a general noise reaction scheme which can be used for hypothesis testing in noise epidemiology considering the cause-effect (Babisch, 2002).